An Efficient Intrusion Detection Method Based on Dynamic Autoencoder - Zhao, Ruijie; Yin, Jie; Xue, Zhi; Gui, Guan; Adebisi, Bamidele; Ohtsuki, Tomoaki; Gacanin, Haris; Sari, Hikmet (IEEE Wireless Communications Letters, 2021)
The proliferation of wireless sensor networks (WSNs) and their applications has attracted remarkable growth in unsolicited intrusions and security threats, which disrupt the normal operations of the WSNs. Deep learning (DL)-based network intrusion detection (NID) methods have been widely investigated and developed. However, the high computational complexity of DL seriously hinders the actual deployment of the DL-based model, particularly in the devices of WSNs that do not have powerful processing performance due to power limitation. In this letter, we propose a lightweight dynamic autoencoder network (LDAN) method for NID, which realizes efficient feature extraction through lightweight structure design. Experimental results show that our proposed model achieves high accuracy and robustness while greatly reducing computational cost and model size.